STRATEGIES FOR DEVELOPMENT OF BEEF CATTLE FARMING BASED ON INNOVATION TECHNOLOGY AND FEEDING PROGRAM TO MEET SELF SUFFICIENCY IN MEAT - Romziah S.; Hario P. S.; Tri Bhawono D. (UPT Penerbitan Universitas Jember, 2016)
Innovation and technology of feed supply for the beef cattle ration by using soy bean cake, pollard and corn oil, and it’s was combined with urea-fibrolite-molasses candy for cattle were significantly (p<0.05) increase the life weight gain of Rambon (Indonesian native beef cattle) as well as the utilization of feed were more efficient. When evaluated of the dressing percentage of the carcass and meat weight, these combination types of beef cattle feed bring a positive prospect for improving the performance of Rambon beef cattle.